2021
DOI: 10.3389/fphys.2021.712281
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y: An Update on the Mechanism Underlying Chronic Intermittent Hypoxia-Induced Endothelial Dysfunction

Abstract: Endothelial dysfunction (ED) is a core pathophysiological process. The abnormal response of vascular endothelial (VE) cells to risk factors can lead to systemic consequences. ED caused by intermittent hypoxia (IH) has also been recognized. Neuropeptide Y (NPY) is an important peripheral neurotransmitter that binds to different receptors on endothelial cells, thereby causing ED. Additionally, hypoxia can induce the release of peripheral NPY; however, the involvement of NPY and its receptor in IH-induced ED has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 114 publications
0
6
0
Order By: Relevance
“…The imbalance between oxidizing and antioxidant defense systems contributes to the activation of oxidative stress, which is manifested as enhanced levels of ROS and MDA, causing endothelial activation and eventually leading to VED [ 32 , 33 ]. The occurrence of VED facilitates increased vascular resistance, leading to vascular diseases, including coronary artery disease, cerebrovascular disease and peripheral artery disease [ 3 , 34 , 35 ]. In our study, ginsenoside Rg1 treatment reversed the downregulated mitochondrial membrane potential in HCAECs and the upregulated level of mitoROS in aortas and HCAECs exposed to CIH.…”
Section: Discussionmentioning
confidence: 99%
“…The imbalance between oxidizing and antioxidant defense systems contributes to the activation of oxidative stress, which is manifested as enhanced levels of ROS and MDA, causing endothelial activation and eventually leading to VED [ 32 , 33 ]. The occurrence of VED facilitates increased vascular resistance, leading to vascular diseases, including coronary artery disease, cerebrovascular disease and peripheral artery disease [ 3 , 34 , 35 ]. In our study, ginsenoside Rg1 treatment reversed the downregulated mitochondrial membrane potential in HCAECs and the upregulated level of mitoROS in aortas and HCAECs exposed to CIH.…”
Section: Discussionmentioning
confidence: 99%
“…The model of CIH exposure established in this study was reported previously ( Jiang et al, 2020 ). Briefly, the mice were exposed to cages of automated, computer-controlled O 2 concentration exchange systems (Proox-100, Shanghai Tow-Int Tech Ltd.) to achieve a similar oxyhemoglobin saturation (SpO 2 ) nadir (50∼60%) in moderate to severe patients based on previous studies ( Zhou et al, 2014 ; Hu et al, 2021 ; Li et al, 2021 ). The mice were exposed to 20 hypoxic events/h (90 s of 21% O 2 and 90 s of 10% O 2 ) for 8 h/day for 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies suggest that hypoxia causes structural and functional alterations in the brain endothelium via different mechanisms, including rearrangement of the endothelial cytoskeleton, altering intercellular adhesions of endothelial cells, and promoting endothelial constriction, apoptosis, and degeneration [141]. Studies of intermittent hypoxia suggest that endothelial cell resistance is reduced due to ROS-dependent activation of the extracellular signal-regulated kinase (ERK1/2) pathway and c-Jun N-terminal kinase (JNK)-mediated re-arrangement of the endothelial cytoskeleton, including the redistribution of actin stress fibers and VE-cadherin, leading to abnormal endothelial barrier function [142,143].…”
Section: A Forward-feedback Loop Between Hypoxia and Endothelial Dysf...mentioning
confidence: 99%